2014
DOI: 10.1186/s13567-014-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuned characterization of Staphylococcus aureus Newbould 305, a strain associated with mild and chronic mastitis in bovines

Abstract: S. aureus is a major aetiological agent of ruminant mastitis worldwide. The chronic nature of S. aureus mastitis makes it difficult to cure and prone to resurgence. In order to identify the bacterial factors involved in this chronicity, Newbould 305 (N305), a strain that can reproducibly induce mild and chronic mastitis in an experimental setting, was characterized in depth. We employed genomic and proteomic techniques combined with phenotype characterization, in order to comprehensively analyse N305. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Several studies reported links between biofilm formation, CP expression and internalization capacity to chronicity in bovine IMI. However, these studies are based on well-established mastitis reference strains, such as RF122 and Newbould 305 26 , or on strains derived from different local or clonal (CC) origin 15 , 27 , while data from studies addressing differences of specific phenotypic and virulence traits of persistent strains in the context of within-herd prevalence are still lacking. To gain insights into the mechanism allowing S. aureus to spread and successfully persist within a herd, this study focuses on isolates collected over a 3-years period from a single dairy herd, which differed in their within-herd prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported links between biofilm formation, CP expression and internalization capacity to chronicity in bovine IMI. However, these studies are based on well-established mastitis reference strains, such as RF122 and Newbould 305 26 , or on strains derived from different local or clonal (CC) origin 15 , 27 , while data from studies addressing differences of specific phenotypic and virulence traits of persistent strains in the context of within-herd prevalence are still lacking. To gain insights into the mechanism allowing S. aureus to spread and successfully persist within a herd, this study focuses on isolates collected over a 3-years period from a single dairy herd, which differed in their within-herd prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…And more, the presence of protein variations for both groups of strains suggests a different affinity for fibronectin, necessary for the internalization of Staph. aureus into host cells [23]. …”
Section: Discussionmentioning
confidence: 99%
“…aureus strains. More recently, Peton and co-workers [23] described a fine-tuned characterization of Staph. aureus Newbond 305, a strain belonging to ST115 and associated to bovine mastitis, by genomic and proteomic comparison with the reference strain RF122.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine strain RF122 was isolated from a case of clinical mastitis 61,62 . Bovine strain Newbould 305 (N305) was shown to reproducibly induce mild and chronic mastitis in bovines 63,64 . RF122 and N305 were kindly provided by Pr Ross J. Fitgerald (Edinburgh Infectious Diseases, Roslin Institute, University of Edinburgh, UK) and Dr Pascal Rainard (ISP, INRAE, Nouzilly France), respectively.…”
Section: Methodsmentioning
confidence: 99%